2017
DOI: 10.1080/00325481.2017.1383819
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the gut microbiota: a focus on treatments for irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS), which is characterized by recurrent abdominal pain and disordered bowel habits, is one of the most common functional bowel disorders. IBS is a substantial burden on both patient health-related quality of life and healthcare costs. Several pathophysiologic mechanisms have been postulated for the occurrence of IBS, including altered gastrointestinal motility, visceral hypersensitivity, changes in gut permeability, immune activation, gut-brain dysregulation, central nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 120 publications
(163 reference statements)
0
50
0
2
Order By: Relevance
“…The effects of antidepressants, anxiolytics, and even antipsychotics in the treatment of IBS also hint at the correlations between IBS and psychiatric disorders. The recent development of probiotics also found that gut flora could play a role in the development and management of IBS …”
Section: Discussionmentioning
confidence: 99%
“…The effects of antidepressants, anxiolytics, and even antipsychotics in the treatment of IBS also hint at the correlations between IBS and psychiatric disorders. The recent development of probiotics also found that gut flora could play a role in the development and management of IBS …”
Section: Discussionmentioning
confidence: 99%
“…The etiology for irritable gut should be multifactorial and heterogenous, and no consistent biomarker or unifying framework has been available to explain the diverse symptoms and findings in IBS . Recently, gut dysbiosis has been proposed as a player in IBS . Variations of microbial composition, function and metabolism have been demonstrated in IBS, particularly those with a diarrhea‐predominant subtype …”
Section: Introductionmentioning
confidence: 99%
“…Recently, gut dysbiosis has been proposed as a player in IBS . Variations of microbial composition, function and metabolism have been demonstrated in IBS, particularly those with a diarrhea‐predominant subtype …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the gut microbiota has been recognized to be critical in influencing the in vivo therapeutic effects of herbal medicines [47,48]. Gut microbiota analysis with 16S rDNA amplification sequencing revealed significant differences in the overall structure of the gut microbiota between different experimental groups, especially in rats of the model group compared with those in the control group.…”
Section: Discussionmentioning
confidence: 99%